1982
DOI: 10.2337/diacare.5.3.203
|View full text |Cite
|
Sign up to set email alerts
|

A Glucose Electrode Using High-Stability Glucose-Oxidase Collagen Membranes

Abstract: A very sensitive glucose electrode was developed using a glucose-oxidase membrane and an anodically polarized platinum disk. Calibration curves were linear over 4.5 concentration decades. It was adapted for human blood samples. The lifetime of glucose-oxidase collagen membranes was greater than 3 yr at 4 degrees C and was approximately 6 mo at 20-30 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…After 5 days of continuous operation at 37 °C in whole blood samples, replenished every 24 h, the calibration slope had changed to 13.6 nA/mM. The variability in slope may represent a change in electrode response over time, as others have reported (34,35); however, the variability in mass transport rates due to differing blood viscosity, electrode positioning, and stirring rates makes the source of variation uncertain in this study.…”
Section: Resultsmentioning
confidence: 80%
“…After 5 days of continuous operation at 37 °C in whole blood samples, replenished every 24 h, the calibration slope had changed to 13.6 nA/mM. The variability in slope may represent a change in electrode response over time, as others have reported (34,35); however, the variability in mass transport rates due to differing blood viscosity, electrode positioning, and stirring rates makes the source of variation uncertain in this study.…”
Section: Resultsmentioning
confidence: 80%
“…Bovine serum albumin (BSA) (1,3,6,7), gelatin (20), or collagen (2,8) are frequently used in enzyme immobilization techniques (21). They bring to the enzyme a proteic environment which seems favorable for its stability (11). As CA membranes usually possess low levels of accessible hydroxyl groups for covalent enzyme coupling, we have decided to increase the number of reacting groups by first covalently coupling BSA to CA (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless two difficulties may be encountered: low levels of activatable or activated surface groups on the support and denaturation of enzyme if covalent coupling is accomplished through functional groups of the enzyme which are essential to its catalytic activity. Highly active and stable membranes may be prepared by acyl azide activation of reconstituted collagen films (2,11). However such membranes have been found to be too thick and too fragile, especially at 37 °C, to be recommended for in vivo applications of enzyme electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various methods that we have studied for preparation of glucose oxidase (GOD) membranes, namely entrapment in cellulose acetate (CA) membranes (Tallagrand et al, 1988) and covalent coupling to collagen by the acyi-azide procedure (Thevenot et al, 1978(Thevenot et al, , 1979(Thevenot et al, , 1982Sternberg et al, 1980), coupling to CA by carbonyldiimidazole (CDI) (Cherifi, 1986), or by bovine serum albumin (BSA) parabenzoquinone (PBQ) linkage (Sternberg et al, in press), we have found that the latter method gives the most suitable membrane for implantable glucose sensor development. Indeed such CA-BSA-PBQ-GOD membranes are thin (5-25 pm).…”
Section: Introductionmentioning
confidence: 99%